UTILIZATION OF SOCIAL MEDIA FOR MARKETING BY ENTREPRENEURS IN ANAMBRA STATE: CHALLENGES AND OPPORTUNITIES - Ilodigwe, Anthonia Onyinye; Uzoh, Bonaventure Chigozie (African Journal of Social and Behavioural Sciences, 2024)
This study examined the utilisation of social media as a marketing tool in entrepreneurial business in Anambra State. The major aim of this study was to ascertain the use and importance of social media as a marketing tool for entrepreneurial businesses and the need to improve its usage for marketing purposes among entrepreneurs. The sample of the study consisted of 399 entrepreneurs randomly selected from the 21 Local Government Areas of Anambra State. A quantitative questionnaire schedule was used for data collection. Data collected were analysed using descriptive statistics while the study hypotheses were tested using Chi-square statistic. The study found that entrepreneurs in Anambra State makes use of social media platforms for marketing purposes mostly on weekly basis. Findings also showed that entrepreneurs utilized social media for marketing by posting goods available for sale and services rendered on personal profile and timelines and that high cost of advertising social media is the major factor limiting the use of social media for marketing purposes among entrepreneurs in Anambra State. Furthermore, the study found that the way to improve the use of social media for marketing purposes among entrepreneurs is by reducing the cost of running advertisements on social media platforms. Based on these findings, the study recommends that the cost of running advertisement on social media should be regulated and made affordable by government in collaboration with various social media stakeholders assigned to the country so that entrepreneurs can easily afford advertisement plans for boosting their business activities.